Implications for paleomobility studies of the effects of quaternary volcanism on bioavailable strontium: A test case in North Patagonia (Argentina). (September 2020) - Serna, Alejandro; Prates, Luciano; Mange, Emiliano; Salazar-García, Domingo C.; Bataille, Clement P.
Abstract: Strontium isotopes ( 87 Sr/ 86 Sr) are used as geochemical tracers for paleomobility studies because they display predictable and stable patterns in ecosystems primarily controlled by the underlying geological regimes. While bedrock geology is stable over thousands of years, geomorphological processes can influence the 87 Sr/ 86 Sr in ecosystems over archeologically relevant timescales. Among these geomorphological processes, the deposition and reworking of volcanic sediments over Quaternary timescales are little studied but could be an important control of 87 Sr/ 86 Sr variations in many archeological regions. North Patagonia is a key archeological region to address animal and human movements, and an ideal location to test the influence of Quaternary volcanism on 87 Sr/ 86 Sr variation as it is located downwind of major volcanic centers. In this study, we aim to assess the main environmental and geological controls of bioavailable 87 Sr/ 86 Sr and to build a high-resolution isoscape using a machine learning regression framework for forthcoming paleomobility studies. We sampled several locations and analyzed different types of samples ( N = 94). The ratios show a limited range of variation, which is not related to the bedrock geology. Rather, bioavailable 87 Sr/ 86 Sr variations display a progressive increase going eastward (away from the Andes), following dust aerosol deposition and elevation variations (R 2 = 0.71, RMSE = 0.00041). We argue that this trend relates to the deposition and reworking of unradiogenic volcanic sediments by aeolian, fluvial and glacial erosion during the Quaternary. As most of this sediment reworking occurred during glacial periods, the current bioavailable 87 Sr/ 86 Sr variations across the study area likely represent a long-term average that varied little during the Holocene. Consequently, our isoscape provides a solid base for Holocene paleomobility studies in North Patagonia and underlines the importance of Quaternary volcanism processes for interpreting 87 Sr/ 86 Sr data in paleomobility studies in volcanic regions. Highlights: Bioavailable 87 Sr/ 86 Sr does not vary following bedrock geology across North Patagonia. Bioavailable 87 Sr/ 86 Sr follows the deposition and reworking of volcaniclastic sediments. We develop a bioavailable 87 Sr/ 86 Sr isoscape for paleomobility studies across North Patagonia for the Holocene.